The philosophy shop ideas, activities and questions to get people, young and old, thinking philosophically - Worley, Peter; Adamson, Harry; Adamson, Peter; Archer, Alfred; Ayala, Saray; Bartley, Grant; Birch, David; Cave, Peter; Christofidis, Miriam Cohen; Cowell, Philip; Davy, James; Day, Andrew; et al. (Bancyfelin, Carmarthen, Wales Independent Thinking Press, 2012)
A veritable emporium of philosophical puzzles and challenges to develop thinking in all classrooms.
Note continued: Some Sums with Zero (undefined terms) / Peter Worley -- Jack's Parrot / Peter Worley -- Wind-Spell / Peter Worley -- After Thoughts -- Who's the Philosopher? (nature of philosophy) / Nolen Gertz -- Philosophical Poetry / David Birch -- Writing a Philosophy Project / John L. Taylor.
Winner of Education Resources Awards: Educational Book Award 2013. Winner of ForeWord Magazine Book of the Year Award: Philosophy 2012.
Keywords: Philosophy -- Study and teaching (Secondary); Puzzles